Supermajorities and Political Rent Extraction - Björn Kauder; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2015)
Models of political competition portray political candidates as seeking the support of the median voter to win elections by majority voting. In practice, political candidates seek supermajorities rather than majorities based on support of the median voter. We study the political benefits from supermajorities using data from Bavaria, the largest German state. Members of the Bavarian parliament had been permitted to hire relatives as office employees but in the year 2000 the practice was prohibited, with exceptions that allowed continuation of employment of previously hired relatives. The circumstances provide an informative setting to relate political behavior to protection of incumbency. Our results show that the likelihood of politicians to hire relatives increased with the margin of the majority for the incumbent in the previous election. When the majority increased by one percentage point, the likelihood of hiring relatives increased by about one percentage point. Supermajorities thus facilitated political rent extraction.
Keywords: D72; H70; A13; 330; political incumbency; rents; rent extraction; nepotism; supermajority